Efficiency of Food Sector of Pakistan – A DEA Analysis - AFZAL , Muhammad; AYAZ , Maryam (Asian Journal of Empirical Research, 2013)
We used DEA to examine the efficiency of the food sector of Pakistan for the period 2007-2010. The year-wise technical efficiency scores show that the performance of the food producing companies improved over the past four years. The overall efficiency analysis suggests that the industry level technical efficiency scores ranged between 0.5 and 0.8 in the year 2007 which increased to 0.9 in the year 2010. The food industry is most efficient (90.7%) in the year 2010 when the technical efficiency score assuming VRS with output orientation was considered. In the second stage analysis based on OLS, the Model IV was found to be the most feasible one in which the size, age and labor to capital ratio and dummy have significant impact on the technical efficiency. Performance of food sector of Pakistan will improve significantly if modern technology in food production and processing is used that is likely to promote exports.